Efektivitas Pemberian Media Edukasi Gizi Infografis Terhadap Peningkatan Pengetahuan Gizi Terkait Pengaturan Makan Atlet Sepak Bola SSB Kancil Mas Karawang - M. Dzikri Mubarok; Linda Riski Sefrina; Milliyantri Elvandari (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. The purpose of this study was to determine the increase in athletes‘ nutritional knowledge related to eating arrangements through nutrition education using printed infographic nutrition education media that contains material about eating arrangements for athletes and determine the effectiveness of the media used to increase athletes’ knowledge. Materials and Methods. This study used a quantitative approach with experimental research methods and quasi-experimental research types. Respondents of this study were 30 11-year-old soccer athletes with nutritional status categories based on Z-score (IMT/U). Results. The result is that there is a significant increase in athletes‘ knowledge after the intervention (p=0.000), Based on the results of the analysis, there is an increase in the knowledge score from pre-test (50,83 ± 10,9) ke post-test (66,67 ± 8,2), that the infographic media used is effective to increase athletes’ knowledge about good eating arrangements and nutrition for athletes. Conclusion. There is an increase in nutritional knowledge related to eating arrangements in athletes after a nutrition education intervention with printed infographic media, so that the media used is proven effective for increasing athletes' knowledge related to eating arrangements. The limitations of this study are that the period of intervention is quite short and only reviews the increase in knowledge only at the time of the pre-test and post-test so that it is not effective to determine the long-term effects on the attitudes and behaviour of athletes. It is hoped that future research will carry out interventions in a long enough period of time and carry out continuous monitoring to see the long-term effects on athletes.